Superior sinensis tea clones release of GMBS 1, GMBS 2, GMBS 3, GMBS 4, and GMBS 5 - Bambang Sriyadi (Jurnal Penelitian Teh dan Kina, 2011)
Developing of Indonesian green tea with international standards must be supported by availability of exellence sinensis tea plant materials with hight yielding and good quality. Selection mother bush using genetic plant materials of seedling sinensis tea plants at Pasir Sarongge were found 42 exellence mother bushes or 1,35 % from 31.104 bushes collection, but three clones were poor in rooting ability and 11 clones were succeptible to blister blight. We found 28 potential clones with hight yielding, good rooting ability, and resistance to blister blight. Testing material indicated that 15 clones with high yield, good quality, and  good taste. Multi-location tests in three years showed that I.2.167; II.1.1; II.1.46; II.2.157; and II.3.109 clones were high in yielding ability and with good stability in performance and broad adaptability. These clones were officialy release by The Evaluation and Variety Release Committee of the Department of Agriculture on its meeting on March 5, 2009 followed by minister decrees of release of these clones as follows: decree number 1979/Kpts/SR.120/4/2009 concerning release of GMBS 1 clones, 1980/Kpts/SR.120/4/2009 concerning release of GMBS 2 clones: 1981/Kpts/SR.120/4/2009 concerning release of GMBS 3, 1982/Kpts/SR.120/4/ 2009 concerning release of GMBS 4 clones, and 1983/Kpts/SR.120/4/2009 concerning release of GMBS 5.